2014
DOI: 10.3109/09513590.2014.971235
|View full text |Cite
|
Sign up to set email alerts
|

The anti-androgen drug dutasteride renders triple negative breast cancer cells more sensitive to chemotherapy via inhibition of HIF-1α-/VEGF-signaling

Abstract: Our results demonstrate that the SRD5A1-corresponding anti-androgenic drug dutasteride might act as a combinatorial therapeutic option besides standard chemotherapy in highly aggressive TNBC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…It is important to emphasize that while there is approximately 80% overlap between TNBC and the basal breast cancer subtype, these two patterns of disease are not synonymous. Substantial diversity in histology and tumor biology exist within the group of cancers that are negative for all three tumor markers 3,4 , and genetic profiling studies are now defining TNBC subtypes that have varying degrees of chemosensitivity, risk of relapse, and response rates to neoadjuvant chemotherapy 5,7,14 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to emphasize that while there is approximately 80% overlap between TNBC and the basal breast cancer subtype, these two patterns of disease are not synonymous. Substantial diversity in histology and tumor biology exist within the group of cancers that are negative for all three tumor markers 3,4 , and genetic profiling studies are now defining TNBC subtypes that have varying degrees of chemosensitivity, risk of relapse, and response rates to neoadjuvant chemotherapy 5,7,14 .…”
Section: Discussionmentioning
confidence: 99%
“…Anderson Cancer Center 7 . Expression of the androgen receptor (AR) by IHC may therefore play a role in the clinical applicability of TNBC subtyping, and AR expression among TNBC cases opens the door to possible targeted anti-AR therapy for these tumors 911,14,16,17 . The mammary stem cell marker ALDH1 also appears to be prominent in differentiating the genetics of TNBC subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…Another two mRNAs, HIF1A and IL8, both have important role in development of breast cancer (38)(39)(40)(41)(42). Studies have been reported that HIF1A is related to multidrug resistance, including paclitaxel (43)(44)(45). Further clarifying functions of these two lncRNAs might help understand the nature of TNBC and provide novel targets for treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia of tumor microenvironment has been considered to be the primary reason of chemoresistance, and evidences have shown that HIF1α could regulate the cellular response to hypoxic stress by mediating the expression of target genes, which is associated with angiogenesis, resistance, invasion and metastasis [28]. Moreover, inhibition of HIF1α was demonstrated to attenuate metastasis of breast cancer cells and increase the sensitivity of tumors to chemotherapy [29]. Recently, panobinostat (histone deacetylase inhibitor) was shown to reduce hypoxia-induced cisplatin resistance of NSCLC cells by destabilizing HIF1α expression [1], implying that HIF1α may play a key role in the drugresistance of NSCLC.…”
Section: Discussionmentioning
confidence: 99%